Face to face, virtual or blended teaching? Trends in higher education teachers in the post-pandemic context (Praxis Educativa, 2024)
The article presents teaching trends in terms of preferences for teaching modalities for their subjects (face to face, blended or virtual) after having gone through the COVID-19 pandemic, during which it was forced to sustain teaching virtually. An exploratory, descriptive study was carried out, with a non-experimental design, supported by a mixed approach, so that data of a qualitative and quantitative nature were worked with. 169 Argentine university professors participated and responded to a questionnaire in which they were asked about their preferred subject teaching modality, as well as the reasons that justify said choice. The results show a majority choice of blended learning, understood by teachers as a modality that meets the needs of the student, who allows, by combining face-to-face and virtuality, to access certain advantages over pure pedagogical options and ensure higher levels of inclusion.
Keywords: teaching modality, teachers, higher education, post-pandemic